The ambivalence regarding volunteering and reward systems in church settings - Boya, Kgaugelo S. (HTS teologiese studies, 2022)
Traditionally, churches exist to fulfil the ‘great commission’, which is to preach the ‘good news’ to all believers. As the ‘great commission’ finds expression within the Church, numerical growth becomes inevitable. The latter puts pressure on the Church to function in a professional manner. People with requisite knowledge, skills and experience are often needed to manage the church activities. Whilst the Bible alludes to spiritual and heavenly rewards, during and post-earthly services, some of these church managers and other volunteers may sometimes require rewards for their efforts and time. Qualitative research methods in the form of semistructured interviews and content analysis were employed. The research was conducted amongst churches within the Gauteng province, South Africa. A total of 26 church managers were interviewed from participating churches. Responses were received and subsequently analysed. Data were analysed using the Atlas.ti software. The findings indicated that the spirit of volunteerism is fast eroding within churches.Contribution: This research highlighted the plight of church managers as volunteers and stewards in the context of not-for-profit organisations and adds towards the agency theory. Consequently, churches as principals ought to find creative ways to generate sufficient revenue for their volunteers.